Extracellular vesicles in rheumatoid arthritis: emerging roles in progression, diagnosis, and therapeutic development - Liu, Qisong; He, Lili; Wu, Xiaomin; Pan, Xiaohua (Frontiers in Immunology, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder that is pathologically defined by persistent synovitis and systemic inflammation. Currently, the clinical diagnosis and management of RA remain challenging, particularly with respect to early detection, the treatment of refractory cases, and ensuring long-term medication safety. Therefore, it is imperative to deepen our understanding of RA pathogenesis, identify specific biomarkers, and develop innovative therapeutic strategies. This review summarizes the roles and recent advances concerning extracellular vesicles (EVs) in RA progression, diagnosis, and therapeutic development. Research indicates that during RA development, joint-resident cells, immune cells, and relevant body fluids form a complex network in which EV-mediated signaling amplifies inflammatory responses and exacerbates tissue damage. Moreover, studies have shown that EVs isolated from synovial fluid and the circulation of RA patients exhibit significantly altered expression profiles, morphology, or subtype composition. These alterations are closely associated with disease activity, underscoring their potential as diagnostic biomarkers and tools for monitoring disease severity. Regarding therapy, EVs derived from diverse cellular sources have demonstrated promising therapeutic potential in RA. They not only carry bioactive molecules that can modulate RA-associated cells, but also serve as engineered delivery vehicles for targeted therapeutic interventions. In summary, EVs play multifaceted roles in the progression, diagnosis, and treatment of RA. Future research should focus on translating EV-related discoveries into clinical applications, thereby supporting the development of novel strategies for the precise diagnosis and management of RA.